A sanctuary in the hora of Illyrian Apollonia excavations at the Bonjakët site (2004-2006) - Davis, Jack Lee 1950-; Stocker, Sharon R.; Pojani, Iris; Dimo, Vangjel (Lockwood Press, 2022)
"In the years 2004-2006, a joint team from the International Centre for Albanian Archaeology in Tirana, Albania, the Institute of Archaeology in Tirana, and the University of Cincinnati conducted excavations in the plain west of the walls of the ancient Greek colony of Apollonia, a short distance to the southwest of the modern village of Pojan. The site lies almost entirely within a complex of farm buildings known locally as Bonjakët. This volume represents the full publication of the results of three campaigns of excavation at the site. The new excavations discovered and documented a previously unknown monumental temple and have made it possible to describe for the first time the material remains of Greek rituals as practiced at the time of, or not long after, the foundation of Apollonia"--
Keywords: Geschichte 600 v. Chr.-200 v. Chr.; Geschichte 2004-2006; Tempel; Sachkultur; Ausgrabung; Ritual; Apollonia -- Illyrien; Pojani; Apollonia (Albania : Extinct city); Excavations (Archaeology) / Albania / Apollonia (Extinct city); Illyrian antiquities; Classical antiquities; Albania / Antiquities; Apollonia d'Illyrie (Ville ancienne); Fouilles (Archéologie) / Albanie / Apollonia d'Illyrie (Ville ancienne); Antiquités illyriennes; Antiquities; Excavations (Archaeology); Albania; Albania / Apollonia (Extinct city); Aufsatzsammlung